DNA Damage Tolerance Pathways in Human Cells: A Potential Therapeutic Target - Ler, Ashlynn Ai Li; Carty, Michael P. (Frontiers in Oncology, 2022)
DNA lesions arising from both exogenous and endogenous sources occur frequently in DNA. During DNA replication, the presence of unrepaired DNA damage in the template can arrest replication fork progression, leading to fork collapse, double-strand break formation, and to genome instability. To facilitate completion of replication and prevent the generation of strand breaks, DNA damage tolerance (DDT) pathways play a key role in allowing replication to proceed in the presence of lesions in the template. The two main DDT pathways are translesion synthesis (TLS), which involves the recruitment of specialized TLS polymerases to the site of replication arrest to bypass lesions, and homology-directed damage tolerance, which includes the template switching and fork reversal pathways. With some exceptions, lesion bypass by TLS polymerases is a source of mutagenesis, potentially contributing to the development of cancer. The capacity of TLS polymerases to bypass replication-blocking lesions induced by anti-cancer drugs such as cisplatin can also contribute to tumour chemoresistance. On the other hand, during homology-directed DDT the nascent sister strand is transiently utilised as a template for replication, allowing for error-free lesion bypass. Given the role of DNA damage tolerance pathways in replication, mutagenesis and chemoresistance, a more complete understanding of these pathways can provide avenues for therapeutic exploitation. A number of small molecule inhibitors of TLS polymerase activity have been identified that show synergy with conventional chemotherapeutic agents in killing cancer cells. In this review, we will summarize the major DDT pathways, explore the relationship between damage tolerance and carcinogenesis, and discuss the potential of targeting TLS polymerases as a therapeutic approach.